TRANSFORMASI LEGENDA SANGKURIANG DALAM SEKUENSIAL MOZAIK DIGITAL - Anggakarti, Deden Maulana (International Conference on Humanity Education and Society (ICHES), 2024)
This research focuses on the creation of digital mosaic art depicting the transformation of the Sangkuriang legend in sequential form. Traditional mosaic art has undergone substantial changes in its visual expression, particularly through the integration of software technology. The research aims to produce digitally transformed mosaic art, exploring the implications of such transformation within contemporary culture. The research methodology employs a creative experimental approach, incorporating historical and technical studies on mosaic art, digital mosaic design, the digital transformation process, and the creation of transitional digital mosaic works. The research utilizes literature studies and interviews with mosaic art experts and academics as stakeholders. Findings indicate that the creation of digital mosaic art enables the incorporation of digital elements such as animation and visual effects, enriching the narrative fragments of the Sangkuriang story. Positive responses from stakeholders reflect interest in innovation and a deeper understanding of mosaic art evolution through digital technology. In conclusion, the sequential transformation of mosaic art in the digital realm represents a significant development in contemporary fine arts, offering new opportunities for artistic expression, cultural promotion, and the preservation of cultural heritage, particularly in the evolving digital landscape of Indonesia.